PERTUMBUHAN TANAMAN CEPLUKAN (Physalis angulata L.) PADA TANAH TERCEMAR LIMBAH BLEACHING EARTH DENGAN REMEDIASI PUPUK KANDANG - Mhd Nur; Hasan Basri Jumin; Maizal Maizar (DINAMIKA PERTANIAN, 2016)
This research was conducted in experimental field of Agriculture Faculty of Islamic University of Riau. The time of implementation starts from October 2012 until January 2013. The design used is a complete factorial random design, consisting of 2 factors namely L (waste bleaching earth) and K (Pupuk Kandang). Bleaching earth waste consists of 4 treatment levels, L0 = 0 gram / plant, Ll = 10 gram / plant, L2 = 20 gram / plant, L3 = 30 gram / plant. Manure consist of 3 treatment level, Kl = 10 gram / plant, K2 = 20 gram / plant equal to 40 ton / ha, K3 = 30 gram / plant to get 12 combination of treatment. Each treatment was repeated 3 times. Each plant unit consists of 8 plants, 4 plants as sample, thus the total population is 288 plants. Observational data were analyzed statistically and continued BNJ test 5%, Parameter observed Total Leaf Area, Dry weight of plant, Relative Growth Rate, Net assimilation rate and Heavy Metal Content Analysis. Treatment of bleaching earth effluent interaction with manure significantly affected the total observation of leaf area, dry weight of plant, relative growth rate and net assimilation rate. Bleach Earth waste treatment significantly affected all observed parameters, ie total leaf area, dry weight of plant, relative growth rate and net assimilation rate. The manure treatment had a significant effect on all parameters observed, with the use of manure can remediate the content of Cu, Cd and Fe metals.